All Relationships Dissipate Except This: The Attitude-Behavior Link on the Roberts Court - Jeffrey A. Segal (Washington University Journal of Law & Policy, 2017)
This Article identifies several reasons that may explain the observed relationship between the ideology of Supreme Court justices and their voting behavior once on the Supreme Court. Segal measures the ideology of justices using newspaper editorial in prominent papers as they appear between the President’s nomination and the justice’s confirmation by the Senate, while tracking the voting behavior of justices as reported by Segal and Cover. The Article concludes, contrary to belief based on psychology and other sciences, that this relationship between ideology and behavior will continue because of the importance of the Supreme Court in national affairs, and greater participation of interest groups in the political process, among others.
Keywords: Supreme Court; Roberts Court; Attitude-Behavior; Relationships; Study; Ideology